Geographical Distribution of Production in Multiple Plant Operations - Dillon, John D. (Management Science, 1956)
The primary purpose of this report is to point up the interrelations found among selected conflicting company objectives, the criteria by which one may evaluate alternate course of action indicated by each of the stated objectives, and some methods for reducing similar problems to a reasonable size, susceptible of analysis by available mathematical techniques. The problem discussed herein is a real problem, but in order to protect the interests of the company which sponsored this particular study, the entire report is paraphrased, and numbers such as quantities and dollars are deliberately changed.